2020
DOI: 10.3389/fphys.2020.01087
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Receptor for Advanced Glycation End Products in Heat Stress-Induced Endothelial Hyperpermeability in Acute Lung Injury

Abstract: Objective: To study the role of the receptor for advanced glycation end products (RAGE) in endothelial barrier dysfunction induced by heat stress, to further explore the signal pathway by which RAGE contributes to heat-induced endothelia response, and thereby find a novel target for the clinical treatment of ALI (acute lung injury) induced by heatstroke. Methods: This study established the animal model of heatstroke using RAGE knockout mice. We observed the role of RAGE in acute lung injury induced by heatstro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Increased immune cells in BALF could be due to endothelial activation/dysfunction and recruitment of inflammatory cells. Consistent with previous studies ( 14 , 17 ), We have found that there were increased total cells in the BALF in mice subjected to HS. A recent study regarding hyperoxia induced ALI also revealed that pretreatment with Alda-1 reduced hyperoxia induced immune cell infiltration, alveolar damage and lung inflammation and preserved alveolar permeability through the activation of Akt and mTOR pathways ( 35 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Increased immune cells in BALF could be due to endothelial activation/dysfunction and recruitment of inflammatory cells. Consistent with previous studies ( 14 , 17 ), We have found that there were increased total cells in the BALF in mice subjected to HS. A recent study regarding hyperoxia induced ALI also revealed that pretreatment with Alda-1 reduced hyperoxia induced immune cell infiltration, alveolar damage and lung inflammation and preserved alveolar permeability through the activation of Akt and mTOR pathways ( 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…Through HS clearly induces endothelial barrier dysfunction and hyperpermeability (13)(14)(15)(16)(17), the potential role of hydrostatic lung edema formation in HS induced ALI models are otherwise limited. Accumulated ROS also induced lung edema formation through downregulation of alveolar epithelial Na/K-ATPase activity with impaired alveolar fluid reabsorption (81).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive heat exposure and subsequent exposure to harmful substances, such as pro-inflammatory mediators, can increase pulmonary microvascular and epithelial permeability [ 5 ], resulting in the accumulation of large amounts of fluid and proteins in the interstitium and alveolar spaces. The process of abnormal pulmonary edema fluid accumulation impairs alveolar gas exchange, which is an important cause of ALI and respiratory failure related to heatstroke [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%